2021
DOI: 10.3390/nu13020567
|View full text |Cite
|
Sign up to set email alerts
|

Physical Education and the Adoption of Habits Related to the Mediterranean Diet

Abstract: Childhood obesity and sedentary lifestyles are now gaining a foothold in the Western world. The aim of this research was to analyse the influence of physical education classes on a healthy diet (i.e., Mediterranean diet). To this end, psychological constructs derived from the theory of self-determination and the theory of planned behaviour were taken into account, such as the satisfaction and frustration of basic psychological needs, motivation in physical education classes, and social cognition and intention.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
18
0
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 16 publications
(20 citation statements)
references
References 48 publications
(49 reference statements)
0
18
0
2
Order By: Relevance
“…A pesar de que la Educación Física es un entorno facilitador para el aprendizaje y consolidación de conocimientos sobre hábitos saludables (Lirola et al, 2021;Moral-Garcia et al, 2021). Baker et al…”
Section: Resultsunclassified
“…A pesar de que la Educación Física es un entorno facilitador para el aprendizaje y consolidación de conocimientos sobre hábitos saludables (Lirola et al, 2021;Moral-Garcia et al, 2021). Baker et al…”
Section: Resultsunclassified
“…In this way, if the classes are enjoyable, fun and the teacher dedicates time to each student, it will lead to greater student involvement, which will lead to an increase in academic performance (Lirola et al, 2021). However, if PE lessons are tedious, monotonous, and boring, students are likely to develop an animosity toward PE classes, resulting in poor academic performance (Lirola et al, 2021; Trigueros et al, 2020a).…”
Section: Discussionmentioning
confidence: 99%
“…However, at the secondary school level, studies have shown that a high internal motivation towards PE classes is positively related to attitude, intention to be physically active and adopting a positive predisposition towards the Mediterranean diet as a result of a positive mental representation of the Mediterranean diet. In this sense, a study conducted by Lirola et al [ 51 ] in a population of adolescents showed how motivation towards PE classes has a positive influence on attitude, behavioral control and subjective norms, favoring healthy and balanced eating. In the same way, but with regard to the practice of physical activity, a study carried out in a population of adolescents by Trigueros et al [ 8 ] analyzed how motivation towards PE classes was positively related to attitude, behavioral control and subjective norms, and, in turn, attitude, behavioral control and subjective norms showed a positive relationship with regard to the intention to practice PA.…”
Section: Discussionmentioning
confidence: 99%